Application of TOPSIS Method in Condition of the Presence of Spatial Dependence - Michal Bernard Pietrzak (Institute of Economic Research (IER), 2016)
The theme of the paper is focused on the application TOPSIS method in condition of the presence of spatial dependence. The occurrence of positive spatial dependence is embedded in the majority of economic phenomena. According to Tobler's first law of geography, one of the key issues in doing the regional research is considering spatial location. Failure to consider the existing spatial dependence for the analysed phenomena can lead to cognitive errors. Therefore the purpose of this article is to take into account the issue of the consideration of spatial dependence within the TOPSIS method. The realisation of the objective set in the present article allowed the development of the procedure for constructing the spatial taxonomic measure of development sTMD using the TOPSIS method. Spatial dependence will be taken into account by using the potential strength of the interaction between the regions. The spatial taxonomic measure of development (sTMD) calculated by means of the modified TOPSIS method allows to determine the trend in the level of the development of the phenomenon under study, assuming the impact of the spatial mechanisms.The spatial taxonomic measure of development (sTMD) defined in that way has been applied in the analysis of the situation on the labour market in Poland. The study will be carried out for the territo-rial composition of 66 subregions (NUTS 3 level) as of 2013. The research allowed us to assess the situation in 2013 and to identify the trend in the development of the labour market. The analysis appointed to the usefulness of the proposed measure sTMD, which is complementary to the use of the others taxonomic measure in the process of explaining the economic reality. The use of the spatial taxonomic measure of development allows expanding the results by conclusions concerning the trend in development of the analysed phenomenon.
Keywords: C21; J01; O10; 330; numeric taxonomy; TOPSIS; Taxonomic Measure of Development; spatial econometrics; spatial dependence